Formation of Religious Character Through the Islamic Character Building (ICB) Program at SD Lughatuna Bekasi City - Sodik, Mugni; Haris, Abdul; Yazid, Syamsurizal (International Journal of Education, Culture, and Society, 2025)
The purpose of this study is to describe and analyze the formation of religious character through the Islamic character building (ICB) program at SD Lughatuna, Bekasi City. This study uses a qualitative approach with a case study type of research. The subjects of the study were the principal, ICB Coordinator, PAI teachers, and grade VI students. Data collection techniques are carried out by interviews, observations, and documentation. The validity of the data uses source triangulation. The data analysis technique uses the analysis of the interactive model of Miles, Huberman and Saldana. The results of the study show that the formation of students' religious character is carried out through teaching, stories, practices, rewards and punishments, habituation, modeling/imitation and controlling. The teaching process is carried out by integrating character values in learning, hadsith about aqidah and worship, Fiqh, Islamic stories. Habituation is carried out through the implementation of congregational prayers, murajaah of the Qur'an and hadith, speaking and behaving politely, orderly culture and queuing. Modeling is carried out by teachers and school employees by giving good examples directly to students at school. Controlling is carried out by the teachers and parents. Teachers actively communicate and collaborate with parents regarding worship and student behavior at home. Evaluations are carried out periodically and programmatically, both weekly, quarterly and yearly.